Tkaniny w powieści Quo vadis? Henryka Sienkiewicza - Kaczmarek, Zofia (My University, 2017)
Henryk Sienkiewicz’s novel Quo Vadis? is well known for its historical accuracy. The background of the book shows a deepened studies on ancient literary sources conducted by its author. The aim of my paper was to answer a question whether descriptions of textiles in the novel are adequate to the present state of knowledge about ancient textiles. To achieve this goal fragments of literary sources were analyzed along with archaeological textiles found on different sites of former Roman Empire. For the purpose of this article I chose the most intriguing textiles described by H. Sienkiewicz. These are: silk, purple, cotton – the luxury textiles worn or used by the most noble of the novel’s characters, and goat’s hair clothes, woollen and linen textiles worn by other protagonists. The analysis shows that the author’s descriptions fits almost perfectly the information given by ancient literary sources. What is more, the archaeological data confirm the literary sources’ evidence. Of course, as a writer, H. Sienkiewicz was not obliged to follow the historical truth, but by his efforts to do so, he made his story more realistic and believable. The careful choice of textiles to enrich the world of Quo Vadis? reflects the Christian message of the novel. The luxury and colourful textiles are worn by the degenerate elite, dark and simple clothing is reserved for the people who do not care about secular world. Moreover, with his materials descriptions, H. Sienkiewicz creates the popular picture of the ancient Romans’ style and clothing.
Keywords: Recepcja antyku; literatura polska; Tkaniny archeologiczne